LITERATURE STUDY OF WORK ACCOMPANIMENT MUSIC EFFECT ON EMPLOYEE PRODUCTIVITY IN SEVERAL COMPANIES - Lisa, Sofia Nuria; Dwiyanti, Endang (Journal of Public Health Research and Community Health Development, 2022)
ABSTRACTIncreased employee productivity can provide benefits for the company. However, isntability of employee productivity can cause some companies to find losses. Accompaniment music at work can be used as a solution to increase employee productivity. This study aims to determine the effect of accompaniment music at work on employee productivity in few companies. This study used a literature study method by reviewing 16 articles obtained from Google Scholar. The criteria for the articles used in this study discussed topics related to accompaniment music at work and employee productivity in several companies at least the last 10 years. Some data that have been collected will be analyzed using a description analysis flow. The results of the study showed that accompaniment music at work has a significant effect on employee productivity in several companies, that productivity was influenced by work environment factors, work spirit, cooperation, work loyalty, work speed, work stress, workload, fatigue, comfort, education level, age, work experience, gender, training, mental, and physical abilities of employees, as well as the relationship between superiors and subordinates. The form of increased employee productivity after accompaniment music while working are work being completed quickly and the results of the product or goods produced exceeding the target.   ABSTRAK Meningkatnya produktivitas karyawan dapat memberikan keuntungan bagi perusahaan. Namun karena produktivitas karyawan yang cenderung tidak stabil, menyebabkan beberapa perusahaan mengalami kerugian. Musik pengiring kerja dapat dijadikan sebagai salah satu solusi untuk meningkatkan produktivitas karyawan. Penelitian ini bertujuan untuk mengetahui pengaruh musik pengiring kerja terhadap produktivitas karyawan di beberapa perusahaan. Metode penelitian yang digunakan dalam penelitian ini adalah metode studi literatur dengan mengkaji sebanyak 16 artikel yang didapatkan dari google scholar. Kriteria artikel yang digunakan adalah artikel yang membahas mengenai topik yang berhubungan dengan musik pengiring kerja dan produktivitas karyawan di beberapa perusahaan pada 10 tahun terakhir. Beberapa data yang dikumpulkan akan dianalisis menggunakan alur analisis deskripsi. Hasil pengkajian menunjukkan bahwa musik pengiring kerja berpengaruh secara signifikan terhadap produktivitas karyawan di beberapa perusahaan, dimana produktivitas ini dipengaruhi oleh faktor lingkungan kerja, semangat kerja, kerjasama, loyalitas kerja, kecepatan kerja, stress kerja, beban kerja, kelelahan, kenyamanan, tingkat pendidikan, usia, pengalaman kerja, jenis kelamin, pelatihan, mental dan kemampuan fisik karyawan, serta hubungan antara atasan dan bawahan. Produktivitas karyawan dapat meningkat setelah diberi perlakuan mendengarkan musik berupa pekerjaan menjadi cepat selesai dan hasil produk atau barang yang dihasilkan melebihi target.